Exchange rate assessments : CGER methodologies - Lee, Jaewoo (Washington, DC : International Monetary Fund, 2008)
As part of this mandate, since the mid-1990s the IMF Consultative Group on Exchange Rate Issues (CGER) has provided exchange rate assessments for a number of advanced economies from a multilateral perspective, with the aim of informing the country-specific analysis of the IMF's Article IV staff reports and fostering multilateral consistency. These assessments are additional tools at the disposal of the IMF staff country desks, which are responsible for formulating exchange rate assessments as part of the Fund's bilateral surveillance, another of the IMF's core responsibilities.--Publisher's description.
Overview -- Macroeconomic balance approach -- Equilibrium real exchange rate approach -- External sustainability -- Conclusions.
Includes bibliographical references (p. 20-22).
"Jaewoo Lee, Gian Maria Milesi-Ferretti, Jonathan Ostry, Alessandro Prati, and Luca Antonio Ricci."
osa11/06/13
Loans
Keywords: International Monetary Fund. -- Coordinating Group on Exchange Rate Issues; Foreign exchange rates -- Mathematical models